A comprehensive review on facemask manufacturing, testing, and its environmental impacts. (30th June 2022) - Khan, Junaid; E, Netnapa; Mariatti, M; Vilay, V; Todo, M
The coronavirus pandemic (COVID-19) is currently the biggest threat to human lives due to its rapid transmission rate causing severe damage to human health and economy. The transmission of viral diseases can be minimized at its early stages with proper planning and preventive practices. The use of facemask has proved to be most effective measure to curb the spread of virus along with social distancing and good hygiene practices. This necessitates more research on facemask technology to increase its filtration efficiencies and proper disposal, which can be accelerated with knowledge of the current manufacturing process and recent research in this field. This review article provides an overview of the importance of facemask, fundamentals of nonwoven fabrics, and its manufacturing process. It also covers topics related to recent research reported for improved facemask efficiencies and testing methods to evaluate the performance of facemask. The plastic waste associated with the facemask and measures to minimize its effect are also briefly described. A systematic understanding is given in order to trigger future research in this field to ensure that we are well equipped for any future pandemic.